The expression Subject Representation in Brazilian journal articles: an analysis of its occurrence and designative variations - Oliveira, Lais Pereira de [UNESP]; Cabrini Gracio, Maria Claudia [UNESP]; Martinez-Avila, Daniel [UNESP] (Univ Federal Parana, Dept Ciencia & Gestao Informacao, 2020)
Introduction: It deals with subject representation in its theoretical perspective, understood as a fundamental dimension in information organization, focused on the representation of attributes related to the content that are essential to enable the search and retrieval by subject. It aims to analyze the occurrence of the expression subject representation and its designative variations in articles in Brazilian journals on Information Science, as a way to clarify the subject in its terminological perspective and to examine its theoretical basis in literature. Method: It is a descriptive study of a quantitative nature, in the form of bibliographic research and the application of bibliometrics on journal articles retrieved from the Base de Dodos Referencial de Artigos de Periadios em Ciencia da Informacao(BRAPCI database) using the term 'Tratamento Tematico da Informacao (Portuguese term for subject representation). It comprises a corpus of 23 articles that were analyzed individually using Excel spreadsheets and the generation of graphs and tables. Results: It shows the recurrence of the term subject representation in the articles on the topic, with a predominance of the expression in the literature review. It also appears in the title, abstract, and keywords. It reveals the designative variants in Portuguese. Conclusions: It concludes that subject representation hos been consolidated in the Brazilian literature, insofar as it is established as a standard designation for the subject representation dimension in publications.
Keywords: Information organization; Subject representation; Scientific production - Brazil; Bibliometrics; BRAPCI